Calibrating Vissim to Analyze Delay at Signalized Intersections. Issue 1 (2017) - Buck, H. Sebastian; Mallig, Nicolai; Vortisch, Peter
The level of service of an intersection is determined principally by control delay. Accordingly, control delay must be reproduced correctly when microscopic traffic simulation is used to evaluate intersections. This study demonstrated how Vissim could be calibrated for that purpose. Vissim models of four signalized intersections for which data had been collected were built. From these data, information that was extracted on headways, time to pass the intersection, and arrival distribution was used for calibration. Calibration of the headways resulted in car-following parameters for these intersections that differed substantially from the Vissim default values. An adjustment in the vehicle arrival distribution to the observed distribution was also necessary to reproduce the measured delay in the simulation.